Remoção de Cu(II), Ni(II), Cd(II) e Pb(II) de efluentes de indústrias de galvanoplastia usando o sistema híbrido adsorção-eletro-flotação-coagulação - Teixeira, Raimundo Nonato Pereira (2015)
Bodies of water contamination problems have stimulated many researchers around the world in the search for alternatives to solve or minimize the effects caused by discharges of toxic materials to the environment. What is desired, preferably, is that such solutions are economically viable and efficient. Toxic metals on the list of the main contaminants of water bodies. Because these are very dangerous chemicals, this class of materials has led many research groups seeking to achieve avoid contamination of water bodies by this type of material. The wastewater generated by electroplating industries have a high concentration of metal ions, so it should be treated before discharge to receiving waters. The processes using adsorption emerge as one of the research lines most valued by many researchers in order to contribute to this issue. Electrochemical processes have also been tested in the remediation of wastewater contaminated with various pollutants, including toxic metals. Natural clays play an important role in this type of study. Several studies have shown very promising results with the use of such material in the removal of toxic metals. This paper aims to conduct a comparative study of removal efficiency of Cu (II), Ni (II), Cd (II) and Pb (II) from six natural clays Brazilian soil. The clays were used: sodium Clay (AS), green clay (AV), clay chocolate calcium (ACCA), ferric clay (AF), attapulgite (AT) and kaolin (CAU). Balance studies were performed through adsorption isotherms in batch systems. For the balance of studies used monoelementares systems and multielement containing the four metal ions. We have also performed the kinetic study to evaluate the lower equilibrium times. Finally experiments were conducted with hybrid systems which use electrocoagulation-adsorption and coagulation with the purpose of working in a continuous system. The results show that all clays have good adsorption capacity for the four ions. The adsorption equilibrium results were compared with the Langmuir, Freundlich and Temkin. The maximum adsorption capacity obtained from monoelementares solutions were: 50.76 mg.g-1 [AS / Pb (II)], 50.76 mg.g-1 [AV / Cu (II)], 57.14 mg.g-1 [ACCA / Cu (II)], 34.72 mg.g-1 [AF / Cu (II)], 169.4 mg.g-1 [AT / Pb (II)] and 10 29 mg.g-1 [CAU / Cu (II)]. The kinetic model best suited to the experimental data was the pseudo second order. The Webber-Morri diffusion models and Boyd show that adsorption processes occur in more than one step and that in the early days predominates intrafilme diffusion process. The electrocoagulation-clotting experiments associated with adsorption with clays are promising because it promoted an increase in the removal capacity and facilitate the separation of the clay from the aqueous phase. The ion removal capacities of Cu (II) from industrial wastewater using the hybrid system were: 54% [AL / AS] to 45% [Al / ACCA] to 57% [Al / HF] 33% to [AL / AT], 48%